Complications in Classifying Suicide Incitement as a Crime - Matua, Nukri (Journal of Legal Studies, 2023)
The article describes and evaluates Georgian legislation in comparison to foreign legislation, as well as, based on the practical analysis, highlights the critical elements of the actual composition leading to suicide and suicide attempt. The problem of identifying whether a crime leading to suicide, or a suicide attempt qualifies for prosecution before investigative bodies and national courts is the main concern. Because of this, the article analyzes topics covered by European and National Court judgments on human rights. The intricacies of the suicide investigation are explained based on the author's personal professional and practical knowledge, likewise, the conditions that need to be proven all through the case investigations. This article provides an overview of the problems with the current legislative architecture, its weaknesses, and basic suggestions for improving them.